THE EFFECT OF RED BEAN ADDITION ON THE MELTING POWER AND ACCEPTABILITY OF ICE CREAM - Lubis, Sella; Yulinda, Ratna; Putri, Rizky Febriyani (Transpublika Publisher, 2022)
Utilization of red beans to be used as food ingredients is not maximized. Ice cream at room temperature melts easily and has a less soft texture, this is due to several factors, one of which is the emulsifier. To improve the quality of ice cream, researchers use natural emulsifiers in the form of red beans. The aim of this study was to determine the effect of the addition of red beans on the melting power of ice cream and organoleptic properties (color, aroma, taste and texture) of ice cream. The research design was a Completely Randomized Design (CRD) with 5 different treatments of adding red beans to ice cream, namely 0%, 30%, 50%, 70% and 100% with data analysis using the SPSS One way-ANOVA test for normal data, Kruskall-Wallis test for abnormal data, as well as Duncan's advanced test. The results showed that the addition of red beans had a significant effect on melting power (0.00<0.05), color (0.00<0.05), and texture (0.00<0.05). The addition of red beans had no significant effect on aroma (0.41>0.05) and taste (0.011>0.05).